2003
DOI: 10.1136/emj.20.4.335
|View full text |Cite
|
Sign up to set email alerts
|

Acute bacterial gastroenteritis: a study of adult patients with positive stool cultures treated in the emergency department

Abstract: Objectives: To investigate the presenting clinical features of acute bacterial gastroenteritis in adult patients treated as outpatients in the emergency department (ED), and the pathogens responsible in this setting and population; and to identify the frequency with which positive stool culture result changes management.Method: This was a retrospective study of all patients who attended the accident and emergency department of an university affiliated hospital in Hong Kong over a 12 month period, who satisfied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 16 publications
2
39
1
5
Order By: Relevance
“…This study found Shigella in 3% of patients, which was lower than the 10.8% reported in another study (22,23). Campylobacter spp.…”
Section: Discussioncontrasting
confidence: 53%
“…This study found Shigella in 3% of patients, which was lower than the 10.8% reported in another study (22,23). Campylobacter spp.…”
Section: Discussioncontrasting
confidence: 53%
“…8% of stool culture positive patients. 9 Therefore it is important to focus on specific symptoms when sending stool cultures in order to improve the yield. In our study, most patients (91.0%) were already discharged before the stool culture results were available.…”
Section: Discussionmentioning
confidence: 99%
“…Mientras que muchos investigadores refutan el hecho de aceptar a este microorganismo como causa de enfermedad diarreica, los resultados disponibles en la literatura científi ca soportan la conclusión de que algunas cepas con codifi cación genética para determinados factores de virulencia asociados a enteropatogenicidad pueden causar gastroenteritis aguda o crónica con dosis infectantes mayores o iguales a 6-8 log 10 ufc/g, como lo demuestran los estudios de Moyer y Larebb 1988, quienes aislaron Aeromonas en un niño de tres meses con diarrea crónica, los de Altwegg y cols., en 1991, quienes evidenciaron este microorganismo en un adulto con gastroenteritis aguda, así como los de Moyer y cols., 2002, quienes aislaron Aeromonas en las heces de un niño de dos años con gastroenteritis aguda 17,18 . Chang y cols., 2003, al realizar en Hong Kong un estudio longitudinal durante un año en pacientes con EDA que acudían a la sala de emergencia del Hospital "Príncipe de Gales" de ese país, notifi caron el aislamiento de Aeromonas (9%) como agente causal, con resultados similares a los obtenidos en esta investigación 19 . Yang Bai y cols., 2004, identifi can Aeromonas spp en un brote de EDA ocurrido durante un ejercicio militar al sur de China 20 .…”
Section: Discussionunclassified